2013
DOI: 10.4236/ojgas.2013.32019
|View full text |Cite
|
Sign up to set email alerts
|

Virological profile of hepatitis B infection in Black African HBsAg chronic carriers

Abstract: Aims: 1) Describe virological profile of patients followed-up for chronic Hepatitis B virus (HBV); 2) Search for a correlation between cirrhosis and virological profile of patients. Patients and Methods: Retrospective study about 75 HBsAg positive patients followed-up for at least one year in two med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The average age of our patients was 49.2 years. They were 42.3 years old for VHB which is consistent with other studies carried out in Côte d'Ivoire that found an average age of 42 years for chronic carriers of HBs Ag [9] and 40 [10], in France HBV patients had a median age of 44 years [11]. Our HCV patients were on average 51.9 years old, in line with SOMBIE et al who found an average age of 51 ± 6.9 years in HCV patients put on treatment [6] and a study in Morocco where HCV patients were on average 52 years old [12], in Tunisia the average age of HCV patients was 50 years [13] and 53.1 ± 8.1 years in Cameroon [7].…”
Section: Discussionsupporting
confidence: 91%
“…The average age of our patients was 49.2 years. They were 42.3 years old for VHB which is consistent with other studies carried out in Côte d'Ivoire that found an average age of 42 years for chronic carriers of HBs Ag [9] and 40 [10], in France HBV patients had a median age of 44 years [11]. Our HCV patients were on average 51.9 years old, in line with SOMBIE et al who found an average age of 51 ± 6.9 years in HCV patients put on treatment [6] and a study in Morocco where HCV patients were on average 52 years old [12], in Tunisia the average age of HCV patients was 50 years [13] and 53.1 ± 8.1 years in Cameroon [7].…”
Section: Discussionsupporting
confidence: 91%
“…There are several different seromarkers used in the serological diagnosis of hepatitis B, and their presence or absence in a person has various clinical and epidemiological implications. Hepatitis B early antigen (HBeAg), hepatitis B surface antibody (anti-HBs), hepatitis B core antibody (anti-HBc IgG), hepatitis B envelope antibody (anti-HBe), and hepatitis B core IgM antibody (anti-HBc IgM) are all examples of HBV seromarkers (Kao, 2008;Attia et al, 2013;Aktar et al, 2021;Aniche et al, 2022). These markers may appear singly or in different combinations, depending totally on the infection's natural course (Towell & Cowie, 2012).…”
Section: Introductionmentioning
confidence: 99%